Food Safety Law and Education - Bhardwaj, Anurag (JOURNAL OF INDIAN EDUCATION, 2019)
Safe and nutritious food is necessary for a healthy life and to pursue education. However, it is a malady that today’s environment is attuned to unhealthy and unsafe food. In addition to this, pollution caused by unsustainable development and other allied factors has maligned this. As a result, people are afflicted with sickness and ailments. The students, both at school and college level are at a greater risk of losing health. They are prone to glamorous commercials which fascinate them to eat junk and unhealthy food. This necessitates us to think over the issue of food safety measures and the related food safety act if we are really the well-wishers of school and college students. If the students of any grade ail on account of unsafe food, they will not be able to pursue their studies as consistently and pleasurably as they will do if they are healthy. It is, therefore, imperative to assimilate food safety measures with the educational system including curriculum. This paper focuses on Food Safety Laws in India and various initiatives taken by the governments, at national, state and local levels to annex food safety and nutrition to education. Apathetic attitude and lethargy on the part of administrative agencies towards the implementation of laws are to be weeded out so that the physical and mental health of pursuers of education may bloom to the optimum level.